Correlates of Perceived Insecurity: Evidence from Pakistan. Issue 4 (7th June 2019) - Nasir, Muhammad; Rehman, Faiz Ur
Abstract: This study explores the correlates of perceived insecurity among the households in Pakistan. For this purpose, data from the third round of Pakistan Panel Household Survey are merged with terrorist incidents taken from Global Terrorism Database. The results illustrate that objective risk, signified by violence in the district of residence, and victimization play an important role in the formation of perceived insecurity. Moreover, males and residents of rural areas feel more insecure than females and urban residents, respectively. Furthermore, spatial variation in violence indicates that terrorist attacks in the first-order contiguous districts (i.e. the immediate neighbors) are also associated with subjective insecurity. These are crucial findings because behavioral changes, such as perceived insecurity, could force the households to make suboptimal investment decisions. More importantly, since changes in behavioral parameters may be highly persistent, this study cautions that violence in Pakistan may have potentially long-term impacts on social welfare.